The assets perspective the rise of asset building and its impact on social policy - Cramer, Reid.; Shanks, Trina R. Williams; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The economy's struggles to overcome the lingering effects of the Great Recession presented unique but essential questions.The book considers a full range of data which considers how this recent experience has impacted households, providing a thorough and contemporary treatment of how the assets perspective has prompted changes within social policy.
Keywords: Science; Science; Science, general